2016
DOI: 10.1016/j.ecolecon.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Can urban areas help sustain the preservation of open space? Evidence from statewide referenda

Abstract: Statewide referenda for land conservation are likely to entail a disparity between people who vote on the referenda and those who live in proximity to conserved areas, which may lead to a lower probability of passage than a more local referendum. This paper examines trends in voting preferences on statewide land conservation referenda in Rhode Island using precinct-level voting data. We identify two similar referenda in 2004 and 2012 and estimate a first difference spatial regression model that seeks to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The influence of political ideology is also ambiguous as studies have found that liberalness both positively influences support (Mohamed 2007;Altonji et al 2016) and negatively affects support (Lowry and Krummenacher 2017). However, given the high degree of ideological polarization across policy issues and that conservatives are more likely to oppose government intervention in the economy and the taxes that pay for such programs, we expect that those who are more conservative will be less likely to support open space bonds.…”
Section: Datamentioning
confidence: 97%
See 2 more Smart Citations
“…The influence of political ideology is also ambiguous as studies have found that liberalness both positively influences support (Mohamed 2007;Altonji et al 2016) and negatively affects support (Lowry and Krummenacher 2017). However, given the high degree of ideological polarization across policy issues and that conservatives are more likely to oppose government intervention in the economy and the taxes that pay for such programs, we expect that those who are more conservative will be less likely to support open space bonds.…”
Section: Datamentioning
confidence: 97%
“…Deacon and Shapiro 1975, Kahn and Matsusaka 1997, Romero and Liserio 2002, O'Connell 2008, Allen et al 2013. This practice has extended to studies that use aggregate data to explain how land use characteristics of the locations that hold environmental referenda affect voting success (Kline and Wichelns 1994;Howell-Moroney 2004;Solecki, Mason, and Martin 2004;Kline 2005;Kotchen and Powers 2006;Nelson, Uwasu, and Ploasky 2007;Schmidt and Paulsen 2009;Banzhaf, Oates, and Sanchirico 2010;Altonji et al 2016;Lowry and Krummenacher 2017;Lowry 2018). As one recent study summarized, "support for open space and public lands in the United States is exceptionally strong for political, cultural, and economic reasons" (Lowry 2018, 1).…”
Section: Support For Land Preservtion Ballot Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on attitudes toward land preservation in New England and, specifically, Rhode Island (e.g. Altonji et al 2016;Johnston et al 2003;Swallow and McGonagle 2006). The state has had sixty-one local and statewide ballot questions to preserve undeveloped land since 1998 (LandVote 2019).…”
Section: The Context Of the Rhode Island Exit Pollmentioning
confidence: 99%
“…Similarly, studies in the land conservation literature find evidence of spatial clustering between conservation agents and voting outcomes (e.g., Albers and Ando 2003, Heintzelman et al 2013, Altonji et al 2016), but tend not to make causal claims either due to dataset limitations or the scope of the study.…”
Section: Introductionmentioning
confidence: 99%